Measuring the top energy asymmetry at the LHC: QCD and SMEFT interpretations - Basan, Alexander; Berta, Peter; Masetti, Lucia; Vryonidou, Eleni; Westhoff, Susanne (Journal of high energy physics, 2020)
The energy asymmetry in top-antitop-jet production is an observable of the top charge asymmetry designed for the LHC. We perform a realistic analysis in the boosted kinematic regime, including effects of the parton shower, hadronization and expected experimental uncertainties. Our predictions at particle level show that the energy asymmetry in the Standard Model can be measured with a significance of 3σ during Run 3, and with more than 5σ significance at the HL-LHC. Beyond the Standard Model the energy asymmetry is a sensitive probe of new physics with couplings to top quarks. In the framework of the Standard Model Effective Field Theory, we show that the sensitivity of the energy asymmetry to effective four-quark interactions is higher or comparable to other top observables and resolves blind directions in current LHC fits. We suggest to include the energy asymmetry as an important observable in global searches for new physics in the top sector.
Gesehen am 24.02.2021